الاستصحاب عند الإمام ابن العربي من خلال كتابه: " المسالك في شرح موطأ مالك - عبابة, الطاهر (جامعة الوادي University of Eloued, 2016)
يبدأ المقال بمقدمة تطرح إشكالا: كيف قَعَّــدَ ابن العربي لأصل الاستصحاب في كتابه المسالك؟ وكيف طبَّقَ وفَرَّعَ على قواعده (الاستصحاب) المختلفة؟ وللإجابة على الإشكال المرفوع، عالجت موضوع الاستصحاب من خلال استقراء قواعده، وأمثلة تطبيقية له من كتاب: "المسالك في شرح موطأ مالك" للإمام ابن العربي، بعد التعريف بإيجاز بابن العربي وكتابه المسالك، قَدّمْتُ للموضوع بتعريف الاستصحاب، وذكر أقسامه وحجيته في مبحث تمهيدي، ثم قسمت قواعد الاستصحاب إلى أربعة مباحث: قواعد تتضمن معنى اليقين، ومبحث آخر عن قواعد تتعلق بالألفاظ.أما المبحث الثالث: لقواعد تتعلق بحال الناس. ومبحث أخير: في قواعد تتعلق بالأبضاع والصفات والعقود. يبرز المقال عناية ابن العربي بالتقعيد والتأصيل -بشكل لافت في كل الكتاب-حيث برع ابن العربي في التقعيد بالاستصحاب، معملا العديد من قواعده. ABSTRACT: This article starts with an introduction explaining how Ibn Al Arabi established the foundation of accompanying in his book Al Massalek, and how he applied it and found derivations from its different rules. To answer the question posed, I discussed the rules of accompanying and some practical examples from Al Imam Ibn Al Arabi’s book Al Massalek. After a brief biography of Ibn Al Arabi and his book Al Massalek, I defined accompanying and discussed its branches and arguments in an introductory chapter. Next, I divided the rules of accompanying into four sections: rules dealing with certainty; a section dealing with the rules related to vocabulary; a third section devoted to the rules of the state of people; and a fourth section discussing the rules connected to vulvas, qualities and contracts. This article highlights the great importance that Ibn Al Arabi gave to the establishment of the rules and principles of accompanying –in all his book in a remarkable way. In fact, he managed to establish rules through accompanying, and provided many practical examples about that.
Imam Ibn Al Arabi’s Accompanying Through His Book Al Massalek For Explaining Muata Imam Malek.
Keywords: الاستصحاب، ابن العربي، القواعد الفقهية، القواعد الأصولية، شرح الموطأ; istis-hab – Ibn alarabi- Jurisprudential rules- fundamental rules -Explanation of Muwatta.